HISTORICAL MILESTONES IN THE DEVELOPMENT OF THE INSTITUTE OF PHYSICAL CULTURE, SPORT AND YOUTH POLICY OF THE URAL FEDERAL UNIVERSITY NAMED AFTER THE FIRST PRESIDENT OF RUSSIA B.N. YELTSIN - Rapoport, L.A.; Markova, A.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was historical analysis of the formation and development of the Institute of Physical Culture, Sports and Youth Policy of the Ural Federal University named after the First President of Russia B.N. Yeltsin. Results and conclusions. The article reveals the history of the formation and development of physical education of students, and then the training of qualified personnel in the field of physical culture and sports in one of the largest universi- ties in the Urals - UrFU. There is an interrelation between the trends in the development of an institution of higher profes- sional education, the formation of student sports and the areas of training specialists for the Sverdlovsk region.